Exploring the Contributions of Artisans to the Cultural and Historical Identities of Wolaita People - Sana, Santime Sagaye; Balcha, Paulos; Haile, Tensay; Tesfaye, Eshetu; Moja, Demisse; Haile, Tesfaye; Shirko, Abesha (Advances in Social Sciences Research Journal, 2023)
The objective this study is to explore the contributions of artisans, especially potters, smiths, and tanners, for historical and cultural identities of Wolaita people. The researchers used qualitative approach for data collection and analysis inline with study objectives. Observation, key informants interview, focus group discussions (FGD), and case study methods were used to collect field data and secondary data were collected from published and unpublished sources. The findings imply that artisans are producing the early hunting and gathering tools, agricultural and war implements, the earl local currency termed as Marccuwaa, cultural costumes, music, and musical implements and providing ceremonial services to the entire people of Wolaita. This confirms that artisans (potters, smiths, and tanners) play the pivotal roles for preservation and promotion of cultural and historical identities of Wolaita people. However, though the entire people are widely using artisan products as the part of their cultural and historical identities artisans were subjected to the existing marginalization and taking the lesser societal recognition. Because of this, artisans were socially disrespected, economically disadvantaged, and historically disfavored in the context of Wolaita. Therefore, the issue needs strategic approach to create societal awareness about the contribution of artisans to Wolaita people in general otherwise it is difficult to improve the life conditions of artisan groups. Not only this but also it will put the sustenance of cultural and historical identities of Wolaita people under question.